An AI-headband for students: a chinese case - Larchenko, Victoriya (Національний технічний університет "Харківський політехнічний інститут", 2025)
У тезах розглянуто кейс, застосування AI-headband у шкільній освіті в Китаї. Головною задачею було виявити мету цього, цільову аудиторію, просування та результат впливу на школярів, їх батьків та вчителів. The thesis examines the case of AI-headband application in school education in China. The main task was to identify the goals for this, the target audience, promotion, and the impact on school students, their parents and teachers.
Keywords: AI-обідок; Китай; освіта; студент; відстеження; суворе батьківство; AI-headband; China; education; student; monitoring; tiger parenting